2017
DOI: 10.1128/jb.00100-17
|View full text |Cite
|
Sign up to set email alerts
|

Uncharacterized Bacterial Structures Revealed by Electron Cryotomography

Abstract: Electron cryotomography (ECT) can reveal the native structure and arrangement of macromolecular complexes inside intact cells. This technique has greatly advanced our understanding of the ultrastructure of bacterial cells. We now view bacteria as structurally complex assemblies of macromolecular machines rather than as undifferentiated bags of enzymes. To date, our group has applied ECT to nearly 90 different bacterial species, collecting more than 15,000 cryotomograms. In addition to known structures, we have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 74 publications
3
16
0
Order By: Relevance
“…These changes are consistent with what would be expected from a reduction in PG thickness in swarming cells. We also observed that the length of polysaccharides was reduced in swarming cells, which would not obviously lead to large changes in cell elongation during osmotic shifts if the organization of PG in these cells follows what is known about the structure of PG in E. coli cells (33): polysaccharides reported to be arranged circumferentially around cells with the peptide cross-links oriented parallel to the long axis of cells. Instead, we expect that a decrease in polysaccharide length makes swarmer cells more prone to changes in diameter.…”
Section: Discussionsupporting
confidence: 52%
“…These changes are consistent with what would be expected from a reduction in PG thickness in swarming cells. We also observed that the length of polysaccharides was reduced in swarming cells, which would not obviously lead to large changes in cell elongation during osmotic shifts if the organization of PG in these cells follows what is known about the structure of PG in E. coli cells (33): polysaccharides reported to be arranged circumferentially around cells with the peptide cross-links oriented parallel to the long axis of cells. Instead, we expect that a decrease in polysaccharide length makes swarmer cells more prone to changes in diameter.…”
Section: Discussionsupporting
confidence: 52%
“…Such ribbons were absent in wild-type or other mutant tomograms and may represent a terminal organelle substructure that has failed to fold or localize correctly in the absence of the paired rods of the core, which may serve to orient normal core assembly. Perhaps significantly, segmented filamentous structures, sometimes bundled, were also recently described in other bacteria (Dobro et al, 2017).…”
Section: Resultsmentioning
confidence: 64%
“…It has long been suggested that the presence of the peptidoglycan layer and the size of the periplasm (15-20 nm) are not compatible with vesicular transport. Although periplasmic vesicular structures have recently been observed in cryo-tomograms, they were largely found in cells showing signs of envelope stress and may have limited physiological relevance (10). It has also been hypothesized that lipid transport can occur in membrane adhesion zones between the IM and the OM (11).…”
Section: Mechanistic Models For Lipid Transport Across the Periplasmmentioning
confidence: 99%